Effect of a Birthing on Country service redesign on maternal and neonatal health outcomes for First Nations Australians: a prospective, non-randomised, interventional trial. Issue 5 (May 2021) - Kildea, Sue; Gao, Yu; Hickey, Sophie; Nelson, Carmel; Kruske, Sue; Carson, Adrian; Currie, Jody; Reynolds, Maree; Wilson, Kay; Watego, Kristie; Costello, Jo; Roe, Yvette
Summary: Background: There is an urgency to redress unacceptable maternal and infant health outcomes for First Nations families in Australia. A multi-agency partnership between two Aboriginal Community-controlled health services and a tertiary hospital in urban Australia designed, implemented, and evaluated the new Birthing in Our Community (BiOC) service. In this study, we aimed to assess and report the clinical effectiveness of the BiOC service on key maternal and infant health outcomes compared with that of standard care. Methods: Pregnant women attending the Mater Mothers Public Hospital (Brisbane, QLD, Australia) who were having a First Nations baby were invited to receive the BiOC service. In this prospective, non-randomised, interventional trial of the service, we specifically enrolled women who intended to birth at the study hospital, and had a referral from a family doctor or Aboriginal Medical Service. Participants were offered either standard care services or the BiOC service. Prespecified primary outcomes to test the effectiveness of the BiOC service versus standard care were the proportion of women attending five or more antenatal visits, smoking after 20 weeks of gestation, who had a preterm birth (<37 weeks), and who were exclusively breastfeeding at discharge from hospital. We used inverse probability of treatment weighting to balance confounders and calculate treatment effect. This trial is registered with the Australian New Zealand Clinical Trial Registry, ACTRN12618001365257. Findings: Between Jan 1, 2013, and June 30, 2019, 1867 First Nations babies were born at the Mater Mothers Public Hospital. After exclusions, 1422 women received either standard care (656 participants) or the BiOC service (766 participants) and were included in the analyses. Women receiving the BiOC service were more likely to attend five or more antenatal visits (adjusted odds ratio 1·54, 95% CI 1·13–2·09; p=0·0064), less likely to have an infant born preterm (0·62, 0·42–0·93; p=0·019), and more likely to exclusively breastfeed on discharge from hospital (1·34, 1·06–1·70; p=0·014). No difference was found between the two groups for smoking after 20 weeks of gestation, with both showing a reduction compared with smoking levels reported at their hospital booking visit. Interpretation: This study has shown the clinical effectiveness of the BiOC service, which was co-designed by stakeholders and underpinned by Birthing on Country principles. The widespread scale-up of this new service should be prioritised. Dedicated funding, knowledge translation, and implementation science are needed to ensure all First Nations families can access Birthing on Country services that are adapted for their specific contexts. Funding: Australian National Health and Medical Research Council.